Decomposing liquidity along the limit order book - Rakowski, David; Wang Beardsley, Xiaoxin (Journal of Banking & Finance, 2008)
In this paper, we estimate the asymmetric information and order processing components of liquidity at extended depths along the limit order book. Using data from the INET ECN, we find that the asymmetric information component decreases as depth increases. Inactive stocks have more information asymmetry at the inside quotes, but it decreases more rapidly along the book than for active stocks. The order processing component of liquidity has fixed and variable constituents, consistent with a fixed cost per order as well as a variable portion based on the size of the order.